Mapping Kebugaran Jasmani dan Kemampuan Motorik Siswa Sekolah Dasar di Era Aktivitas Minim Gerak - Karlina Dwijayanti; Arif Rohman Hakim; Rima Febrianti; Fadlan Alfin (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aims to describe the level of physical fitness and motor skills of elementary school students. The method used is quantitative research with a survey design, involving 60 students as subjects through a total sampling technique. Data collection instruments include the TKJI Instrument used through several types of tests, namely the 40-meter run, the hanging arm strength test with bent elbows, the abdominal muscle strength test while sitting, the explosive power test of the leg muscles in the vertical jump, and the 600-meter running endurance test, as well as motor skills tests that include the standing stork test, sprinting, ball throwing, and shuttle run test. The results of the study indicate that the level of physical fitness of students is in the moderate category with an average value of 14.40 and a percentage of 48%. Meanwhile, students' motor skills are also classified as moderate with an average value of 31 and a percentage of 52%. Overall, this study concludes that the level of physical fitness and motor skills of elementary school students are in the moderate category.